Cumulative Childhood Maltreatment and Executive Functioning in Adulthood. Issue 4 (21st April 2021) - Letkiewicz, Allison M.; Weldon, Anne L.; Tengshe, Chinmayi; Niznikiewicz, Michael A.; Heller, Wendy
ABSTRACT: Maltreatment during childhood has detrimental consequences for survivors. Among children, maltreatment predicts deficits in cognition and impairment in academic and emotional functioning. Although studied extensively in children, the extent to which cognitive deficits are evident in adulthood has been examined to a lesser extent. Executive functioning (EF) is a set of cognitive processes that help to guide behavior toward goals and is characterized by a prolonged maturational time course. As such, it is particularly vulnerable to the effects of early stress, which confers risk for psychopathology. Thus, it is critical to assess the potential impact of childhood trauma on adult EF. The present study sought to assess the impact of a history of childhood maltreatment on EF during adulthood using both self-reported and task-based measures of EF processes. Higher levels of cumulative childhood maltreatment predicted poorer EF. Furthermore, deficits were not accounted for by current symptoms of depression and anxiety, indicating that the impact of childhood maltreatment on cognitive functioning in adulthood is not the result of current internalizing psychopathology.